EFEK PENAMBAHAN EKSTRAK ETANOL HERBA CIPLUKAN (PHYSALIS ANGULATA L) SEBAGAI SUPLEMEN TERAPI PADA RHEUMATOID ARTRITIS - Vikasari, Suci Nar; Sujiatmo, Afifah Bambang; Sukandar, Elin Yulinah; Wahyuningsih, Sri; Solihah, Puspa Sari Dewi; Suryani, Suryani; Aisyah, Salmanda; Kuatrina, Kuatrina; Astuti, Niken Juni; Siftiani, Nindy Dwi (Jurnal Farmasi Indonesia, 2019)
Rheumatoid arthritis is an autoimmune disease characterized with chronic joint inflammation. Chronic inflammation leads to liver function abnormality. Previous study showed that Physalis angulata L. had antiinflammatory, hepatoprotector, and immunosupressan effect. This research aims was to evaluate the effect of ethanol extract of P.angulata as adjuvant on liver function of RA animals model. Animals was induced with 0.1 mL complete freund adjuvant (CFA) intraplantar. The dose of P.angulata extract was 50 mg/kg bw po. The extract was given for 10 days as adjuvant of 0.1125 mg/kg bw methotrexate. Evaluation of liver function consisted of measurement of aminotransferase (AST and ALT), alanine phosphatase (ALP), organ index, and histology. The result showed that CFA could increase the level of AST and ALP and decrease the level of ALT and organ index of control group. The extract of P.angulata as adjuvant of methotrexate could decrease the level of AST and ALP and increase the level of ALT and organ index compare to control group, but could not reach its normal value. Histology showed that the extract also could improve liver regeneration. The extract of P.angulata at dose of 50 mg/kg bw used as adjuvant could improve liver function of RA animals model.